Prevalence and predictors of depression among oncology patients receiving chemotherapy in government hospitals in Peninsular Malaysia - Remesh Kumar, Mamta Vesudave; Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Ismail, Siti Irma Fadhilah; Periasamy, Ummavathy (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Cancer-patients undergoing chemotherapy experience a high level of depression. The objective of this study was to determine the prevalence and predictors of depression in cancer-patients receiving chemotherapy in government hospitals in Peninsular Malaysia. Methods: This research was started with a cross-sectional study among 1356 patients undergoing chemotherapy in 10 government state hospitals in the Peninsular Malaysia. The data were collected using self-administered questionnaires including socio-demographic characteristics, severity of cancer, depression through Patient Health Questionnaire (PHQ-9), social support using the Multidimensional Scale of Perceived Social Support (MSPSS) and hopelessness using the Beck Hopelessness Scale (BHS).The research also con-ducted the descriptive statistics to obtain variable percentages and frequencies. Inferential analysis was also conducted by using chi-square or Fisher’s exact test in determining the relations among variables at the level of significance where p<0.05.Simple logistic regression was applied in determining the crude odd-ratio and variables with p value, where p<0.25, were entered into the multivariate logistic regression model to identify the significant predictors of depression. The best predictor was based on adjusted odds ratio. Results: The prevalence of depression was 34.00%. The significant predictors of depression were age, gender, education level, pain due to chemotherapy, depressed due to cancer, treatment with any anti-depressant, worried of the adverse effect due to cancer treatment, involvement in any cancer support society, level of social support and level of hopelessness. Among all predictors, level of social support was identified as the highest risk of prediction for depression. Conclusion: Findings of the study indicate that the health care services should focus on the management and intervention of depression in cancer-patients.